(untitled) (Czech Journal of International Relations, 1967)
The name of General André Beaufra, director of the Institute of Strategic Studies in Paris and editor-in-chief of the military theoretical review Stratégie, shone in the sky of military-political thinking with the light of a star of the first magnitude. Already in his vigorous book Introduction a la stratégie, Paris 1963, Beaufre demonstrated an indisputable ability to think about strategy at a much higher level of generalization than some seasoned and well-known authors from the USA, England and other countries. It is no coincidence that Lidell Hart, a well-known English theorist in our country, spoke very highly of his Introduction to Strategy, who spoke of it as the best work written in the field of strategy in his lifetime. Perhaps less than a year passed and General Beaufre published a second work, also conceived by Siroc, entitled Deterrence and Strategy. After another spring break, he published the books L’Europe et NATO and La drame de 1940: At the end of last year, he published Stratégte de l’action, Paris 1966. The publication of his thin, but very binding book was met with a strong response from the military press, our reviews refers to Beautre’s second, also very well-worn work.